2020
DOI: 10.1108/tlo-02-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Is the DLOQ learning-oriented leadership isomorphic? Learning-oriented leadership mediates hierarchical teams’ learning dimensions

Abstract: Purpose Learning organizations are often theorized at a team level, yet there is a lack of team-level studies. This study aims to evaluate if team-level dimensions of a learning organizational questionnaire (DLOQ) measures are reliable and reflect real team properties and if both individual-level and team-level DLOQ leadership mediates the effect of rank on other DLOQ measures. Design/methodology/approach An empirical analysis evaluated if team-level DLOQ measures are reliable and reflected real team propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The role of team leaders could be twofold: to establish systems and processes necessary for joint work and learning, and implement a specific culture and climate that, in the context of learning organizations, stimulates dialogue, inquiry, knowledge sharing, experimenting, learning and change. Stothard (2021) found that learning-oriented leadership indeed plays a key role in improving other measures from the questionnaire in hierarchical teams and minimizes the negative effect power asymmetry could have on team performance, including learning. Her finding is pertinent to military teams.…”
Section: Restaurants As Learning Organizationsmentioning
confidence: 88%
See 2 more Smart Citations
“…The role of team leaders could be twofold: to establish systems and processes necessary for joint work and learning, and implement a specific culture and climate that, in the context of learning organizations, stimulates dialogue, inquiry, knowledge sharing, experimenting, learning and change. Stothard (2021) found that learning-oriented leadership indeed plays a key role in improving other measures from the questionnaire in hierarchical teams and minimizes the negative effect power asymmetry could have on team performance, including learning. Her finding is pertinent to military teams.…”
Section: Restaurants As Learning Organizationsmentioning
confidence: 88%
“…When learning-oriented leadership is implemented, even more success regarding team learning and performance could follow. Stothard (2021) postulated that learning-oriented leadership not only benefits team learning and their performance, but also affects other dimensions from the questionnaire. The role of team leaders could be twofold: to establish systems and processes necessary for joint work and learning, and implement a specific culture and climate that, in the context of learning organizations, stimulates dialogue, inquiry, knowledge sharing, experimenting, learning and change.…”
Section: Restaurants As Learning Organizationsmentioning
confidence: 99%
See 1 more Smart Citation